Virtual Outreach (VO) as an effort to increase VCT (Voluntary Counselling and Testing) coverage at PSP (Female Sex Workers) in Semarang Regency - Rokhani Rokhani*; Indri Astuti Purwanti; Achmad Solichan; Rohmatul Fitri Ummumah; Rohmalia Shoffi Salsabila (Universitas Syiah Kuala, 2023)
The high number of HIV / AIDS cases in Indonesia requires the role of all parties to reduce the infection of the disease, one of the efforts to reduce the transmission of HIV / AIDS is to increase the coverage of VCT (Voluntary Counselling and Testing). The program aims to increase VCT coverage by using VO (virtual outreach). The method used in the activity uses the PRA (Parcipatory Rural Apraisal) model, namely by involving all field officers at the Sokoguru Foundation through providing education and training to increase capacity in conducting VO. As a result of this activity, there was a significant difference (p value 0.05) in terms of the knowledge of trainees before and after being given this education and training. In conclusion, the Sokoguru Foundation, which oversees field officers, can routinely increase the capacity of its field officers to conduct virtual outreaches as an alternative in conducting outreach to the Key population.